Case Report: Novel MAGT1 pathogenic variant with significant atopy, hypogammaglobulinemia and viral skin infections - Gunderman, Lauren; Ptak, Christopher P.; Schutt, Madeline; Yahashiri, Kento; Lippner, Elizabeth; Khojah, Amer; Ahmed, Aisha; Khanolkar, Aaruni (Frontiers in Immunology, 2026)
BackgroundX-linked MAGT1 deficiency with increased susceptibility to EBV-infection and N-linked glycosylation (XMEN) disease is an inborn error of immunity (IEI) affecting the Magnesium Transporter 1 (MAGT1) gene. In this report, we present the diagnostic odyssey for a patient harboring a novel MAGT1 variant resulting in XMEN disease.Case presentationA 6y old male child of Caucasian ancestry presented at the immunology clinic in our hospital with a history of recurrent upper respiratory tract infections, as well as significant atopy and viral skin lesions. Genetic testing identified a novel, hemizygous pathogenic variant in the magnesium transporter 1 (MAGT1) gene (c.580dup; p.Ser194Phefs*3). Follow-up testing by flow cytometry revealed the canonical disruption in Natural Killer Group 2D (NKG2D) surface expression on CD8 T cells and NK cells, and clinical testing for congenital disorders of glycosylation (CDG) additionally verified the hallmark defect in glycosylation that underpins XMEN disease. Subsequent in silico analyses using AlphaFold provided an in-depth view of the resulting aberrant protein structural variant and its inability to tether itself to the OST-B complex, a pre-requisite for optimal enzymatic activity of the MAGT1 protein. Disease management included infection control and prophylaxis, steroids and immunotherapy for the patient’s asthma and atopy, topical antiviral treatment for the warts and molluscum, as well as biannual EBV load monitoring (the patient is EBV negative).ConclusionThis case illustrates how a synergistic multi-disciplinary team approach established a diagnosis of XMEN disease in a patient with an atypical clinical presentation. This case also highlights a growing trend where established diagnostic tools such as flow-cytometry and genomics can be complemented with newer, sophisticated analytical approaches such as AlphaFold to further elucidate the functionally crippling effects of novel variants described in the setting of IEI.